Gender diverse boards and goodwill changes: association between accounting conservatism, gender and governance - Schadewitz Hannu; Spohr Jonas (Springer Nature Switzerland, 2022)
We study the relation between board gender diversity and goodwill (GW). GW on the balance sheet is connected to both the firm’s risk-taking and its accounting conservatism which are two popular topics in how gender diversity affects the governance of firms. GW captures the firm’s decision to acquire another business for a price exceeding the received identifiable net assets and the subsequent valuation of the purchase. We propose that board decisions affecting GW could depict information about board gender diversity and its potential effects. Specifically, we examine Nordic listed firms in the period 2009–2018, to determine whether and how female representation on the board of directors is linked to the GW change. Big GW increases are associated with risk-taking and GW write-downs are signs of conservative accounting. Thus, we hypothesize and evidence that firms with substantial GW increases (decreases) are associated with fewer (more) women on the board. These results provide insight on board composition and potentially also on good governance and their consequences for strategic decision-making. Our findings contribute to the board diversity literature in accounting and corporate governance.